2020
DOI: 10.1080/1331677x.2020.1798263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharmaceutical companies’ corporate reputation on drug prescribing intents in Romania

Abstract: This research examines the effect of pharmaceutical companies' (PCs') corporate reputation on drug prescribing intents. The aim is to determine the extent to which the PCs' corporate reputation influences general practitioners' (GPs') drug prescribing intents. This research is based on quantitative analysis using structural equation modelling (SEM) on data collected from a sample of 177 Romanian GPs. The PCs' corporate reputation contributes to build and maintain trust in their products, which in turn influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The study evaluated the effect of DNEB on physicians’ prescription behaviour via DP and DT. The extant literature, though emphasized the importance of informative detailing for new brands (Narayanan and Manchanda, 2009; Ching and Ishihara, 2012; Matikainen et al , 2017; Faisal et al , 2020; Ion et al , 2021; Morgan and Zane, 2022; Rhee and Yi, 2022) and the role of persuasive detailing for established brands (Narayanan and Manchanda, 2009; Ching and Ishihara, 2012). However, there is little prior research on the influence of DNEB on physicians’ prescription behaviour of new and established brands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study evaluated the effect of DNEB on physicians’ prescription behaviour via DP and DT. The extant literature, though emphasized the importance of informative detailing for new brands (Narayanan and Manchanda, 2009; Ching and Ishihara, 2012; Matikainen et al , 2017; Faisal et al , 2020; Ion et al , 2021; Morgan and Zane, 2022; Rhee and Yi, 2022) and the role of persuasive detailing for established brands (Narayanan and Manchanda, 2009; Ching and Ishihara, 2012). However, there is little prior research on the influence of DNEB on physicians’ prescription behaviour of new and established brands.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, World Health Organization (WHO) defines medical drug promotion as "all information and persuasive activities by manufacturers and distributors, the effect of which is to induce the prescription, supply, IJPHM 17,3 purchase and/or use of medicinal drugs" (WHO, 1988). Pharmaceutical companies, while meeting the health needs of the consumers, also strive to generate profits for research, development and sustenance (Ion et al, 2021). Hence, pharmaceutical companies play a crucial role in enabling physicians to make informed choices (Levy, 1994;Menebo, 2021;Vandenplas et al, 2022) and cater to patient needs effectively.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant number of past studies have argued that the marketing strategies of pharmaceutical companies are one of the most influential factors [11][12][13]. The most commonly studied marketing strategies such as medical representatives (MRs), ads in medical journals, the brand of the drug, free drug samples, promotional gifts etc., are effective in swaying the prescribing decisions of physicians [12,[14][15][16]. Murshid and Mohaidinhave reported that a medical representative is a primary source of drug information for physicians, especially in the thirdworld nation [4].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%